STUDI KELENGKAPAN SERTA PEMANFAATAN ALAT DAN BAHAN PRAKTIKUM BIOLOGI DI SMA NEGERI PEKANBARU TAHUN AJARAN 2014/2015 - Melda '; Yuslim Fauziah Fauzia; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the completeness and utilization of lab equipment and materials Biology in High School (SMA) Pekanbaru State, which was conducted in January-March 2015. This research is a descriptive study, with samples from high schools in the city of Pekanbaru. Samples taken by purposive sampling, which consists of 12 schools, namely, SMAN 1, SMAN 2, SMAN 4, SMAN 5, SMAN 6, SMAN 7, SMAN 8, SMAN 9, SMAN 10, SMAN 11, SMAN 13 and SMAN 14. completeness of data collection tools and lab materials using observation sheets and questionnaires closed for the utilization of tools and lab materials were filled by biology teacher from class XI. Data on quantitative descriptive analysis, the completeness of lab equipment and materials consist of three indicators and utilization consists of two indicators which refer to Regulation Permendiknas 24, 2007. The results showed that the completeness of tools and materials lab in SMA Pekanbaru highest mean score obtained SMAN 8 Pekanbaru 2.7 (complete). Lowest score obtained in SMA 13 Pekanbaru 1.5 (incomplete). The effectiveness and efficiency of lab equipment and materials that are in the optimal criteria (80%). Maintenance tools and lab materials are at less than optimal criteria (59.9%). It can be concluded that the completeness of tools and materials lab in SMA Pekanbaru is the complete criteria, with optimal utilization of the categori enough. Key Words: descriptive study, tools and materials Practical Biology, SMA Pekanbaru